Implementation Of Hybrid Filter For Harmonics Reduction In Non-Linear Loads - Yahya Chusna Arif (Green Publisher Indonesia, 2023)
The efficiency of electrical power can be improved by improving power quality. Installing capacitor banks is one way to improve power quality by improving the power factor. On the other hand, the use of non-linear loads is increasing. This load produces a non-sinusoidal waveform which causes harmonics to appear in the electric power system. Harmonic problems will become a serious problem in the power system when there is a capacitor bank in the system which will cause resonance risk at the harmonic frequencies. This resonance problem can be solved by installing a detuned filter. Detuned filters can reduce harmonics and protect the system from the resonance risk. However, the detuned filter installation is not sufficient to reduce all harmonics that generated by non-linear loads, so the system needs to be equipped with an active filter. In this study, using a combination of 14% detuned filter and active filter, each of which is attached parallel to the load. The result of power quality improvement can increase the power factor from 0.6 to 0.88, THDi is reduced from 49.5% to 18%, and THDv is reduced from 2.18% to 1.97% after installing the hybrid filter